2013
DOI: 10.1016/b978-0-444-52891-9.00073-7
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive side-effects of antiepileptic drugs in children

Abstract: Although the causes of cognitive impairment in patients with epilepsy have not been completely elucidated, three factors are clearly involved: the underlying etiology of epilepsy, the effects of seizures or the epileptiform EEG discharges themselves, and the central nervous system effects of antiepileptic drugs (AEDs). All commonly used AEDs have some effect on cognitive function, and the effect may be substantial when crucial functions are involved, such as learning in children. With phenobarbital, there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
0
20

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(111 citation statements)
references
References 95 publications
3
88
0
20
Order By: Relevance
“…A recent study demonstrated that the cognitive side effect profile of lacosamide is comparable to that of LTG and superior to that of topiramate, which was indicated by both subjective and objective measures [43]. VPA does not appear to impair cognition if sufficiently controlled for hyperammonemia [42]; however, studies have shown VPA can reduce spatial working memory and cell proliferation in the hippocampus [44]. These results support the idea that VPA may cause cognitive impairment by reducing neurogenesis within the hippocampus [44].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…A recent study demonstrated that the cognitive side effect profile of lacosamide is comparable to that of LTG and superior to that of topiramate, which was indicated by both subjective and objective measures [43]. VPA does not appear to impair cognition if sufficiently controlled for hyperammonemia [42]; however, studies have shown VPA can reduce spatial working memory and cell proliferation in the hippocampus [44]. These results support the idea that VPA may cause cognitive impairment by reducing neurogenesis within the hippocampus [44].…”
Section: Discussionsupporting
confidence: 68%
“…For example, phenytoin may affect mental speed and phenobarbital may affect attention and memory. Evidence has shown that LTG has a cognitive-enhancing effect on attention [42]. A recent study demonstrated that the cognitive side effect profile of lacosamide is comparable to that of LTG and superior to that of topiramate, which was indicated by both subjective and objective measures [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The evidence is fairly strong with regard to phenobarbital and its association with cognitive deficits in pediatric patients, 6 some data showing phenytoin has an effect on mental speed, while levetiracetam does not seem to have a negative impact on cognition. 7 This is the first study to report the outcomes of post-cardiac surgical pediatric patients who received AED therapy as a result of postoperative seizures. Overall, the use of these agents at our institution is very low, considering that approximately 900 cardiac surgical procedures are performed each year.…”
Section: Discussionmentioning
confidence: 99%
“…Among the main factors there are: 1) the pre-disease condition (e.g., the child's skills and abilities), 2) factors connected with the disease (e.g., the etiology and type of the epilepsy syndrome) (Aldenkamp et al, 2005), 3) the moment when the disease occurred in the context of the child's developmental processes, 4) the duration of the disease, 5) the immediate effect of epileptic activity (e.g., partial seizures vs. generalized, the occur- Table 3. Illustration of the problem on the case of a 12-year-old boy rence of status epilepticus or transient cognitive impairment) (Aldenkamp, 2004), 6) factors associated with the treatment: surgical and/or pharmacological (Ijff andAldenkamp, 2013; Sherman et al, 2003), 7) the absence from school connected with the occurrence of seizures (Aguiar et al, 2007), 8) the profile of cognitive deficits that appear in the course of the disease (Aldenkamp et al, 2005), 9) factors associated with the patient's socio-economical conditions (Fastenau et al, 2004). Of significant meaning for the appearance of school difficulties can also be psychiatric disorders that co-occur with epilepsy (depression, anxiety, or intensified symptoms of attention deficit hyperactivity disorder, commonly known as ADHD) (Reilly, Agnew and Neville, 2011).…”
Section: Specific Learning Difficulties and Epilepsy -A Review Of Stumentioning
confidence: 99%